General surgical unit experience of traumatic vascular injuries in an Australian regional hospital - Silva, Munasinghe; Anandan, Aathavan Shanmuga (International Surgery Journal, 2022)
Background: Vascular trauma is a significant burden to the regional community due to the associated high morbidity and mortality from the complications of the injuries. This may be due to the complexity of the injuries and the issues with initial management at the regional hospitals. Vascular injury management training should improve the outcome of initial surgical management by the general surgical team in regional centres. The study aims to describe the epidemiology and management of vascular injury in regional hospitals in Queensland, Australia. Methods: A retrospective descriptive analysis was performed using the data of patients with traumatic vascular injuries between January 2017 and July 2021 presented to Hervey Bay hospital in Queensland, Australia. Results: Fifty-nine patients with vascular injuries were reviewed. The reported number of penetrating and blunt trauma cases were 43 (72.9%) and 16 (27.1%) respectively, and 42 (71.2%) were males. Most mechanisms of injury were cuts (n=32, 54.2%), followed by falls (n=16, 27.1%) and stabs (n=11, 18.7%). Fifty-one (86.4%) were initially surgically managed regionally, with 21 (35.6%) requiring transfer to a tertiary trauma centre. Outcomes of the incidents resulted in one (1.7%) patient requiring amputation, three (5.1%) needing a fasciotomy and the mortality of two (3.4%) patients. Conclusions: Vascular trauma causes a significant burden to Australian regional hospitals. Identifying injury patterns and common causes for vascular injury will help in early identification and prompt management. Vascular trauma management training should improve the quality of care from the general surgeons in the regional centres.